High voltage beam discharge in nitrogen with fast neutral atom reflection from tantalum cathode - Boldasov, V.S.; Kuzmichev, A.I.; Melnichenko, M.S.; Shulaev, V.M. (Вопросы атомной науки и техники, 2021)
The kinetic simulation of high-voltage beam discharge at low pressure of nitrogen is fulfilled. The characteristics of particle flows to the tantalum cathode and back reflection of fast nitrogen atoms are calculated. The reflection coefficient equals tens of percents at voltages up to 100 kV. The generation of fast nitrogen atoms may be used for metals and dielectrics nitriding with implantation effect. Виконано кінетичне моделювання високовольтного променевого розряду при низькому тиску азоту. Розраховані характеристики потоків частинок до танталового катода і зворотне відбиття швидких атомів азоту. Коефіцієнт відбиття дорівнює десяткам відсотків при напрузі до 100 кВ. Генерація швидких атомів азоту може бути використана для азотування металів і діелектриків з імплантаційним ефектом. Выполнено кинетическое моделирование высоковольтного лучевого разряда при низком давлении азота. Рассчитаны характеристики потоков частиц к танталовому катоду и обратного отражения быстрых атомов азота. Коэффициент отражения составляет десятки процентов при напряжении до 100 кВ. Генерация быстрых атомов азота может быть использована для азотирования металлов и диэлектриков с имплантационным эффектом.